PRESSURE BUILD UP ANALYSIS AND DELIVERABILITY ON WELL GAS HAN-1 MANUALLY AND USING ECRIN SOFTWARE - Wirianta, Hananya; Ridaliani, Onnie; Oetomo, Hari Karyadi (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Well Testing is one of the Method to determine the ability of the layer or formation to produce, Parameter that obtained by it is initial pressure reservoir (Pr), formation damage (s), reservoir boundary and the ability of the well to produce. On Well “Han-1” Field “X” is a type of gas well with carbonate rock formations. Methods that being used on this well is Pressure Build-Up and Delieverabilty Test with using Ecrin Software v.4.02 Result that we get from the test shows us that the permeabilty number is low, negative skin factor shows us that this well has been stimulated. And the type for this reservoir that we get from Ecrin Software is Homogenous, with Changing Wellbore Storage and the boundary is pararel fault. Even tho the Well Testing showing that the permeability score is low the flow of the well is optimal because this well is a gas well.   Quantitatively on the Pressure Build Up Analysis with Horner Method manually result that we get is not so different with Software Ecrin